2019
DOI: 10.1177/1933719119831778
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Placental Position by Early First-Trimester Ultrasound: A Pilot Study

Abstract: Objective: Conventional wisdom is that placental location cannot be identified before 8 weeks’ gestation when the placenta first becomes hyperechogenic on ultrasound. We sought to evaluate whether placental location could be reliably diagnosed between 5 and 6 weeks’ gestation. Materials and Methods: This was a retrospective analysis of prospectively acquired data. Early placental location was diagnosed by evaluation of the embryonal and yolk sac position inside the gestational sac on transvaginal ultrasound. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…In our study, aborted group had significantly higher prevalence of lower abdominal pain, vaginal discharge and itching than complete pregnancy group. This is in agreement with a recent study which reported that women with recurrent pregnancy loss, had higher pelvic pain and vaginal bleeding (7). While the risk of threatening abortion was highest among those who reported abdominal discomfort (55.9%), those who did not report pain (42.6%) nevertheless had an abortion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, aborted group had significantly higher prevalence of lower abdominal pain, vaginal discharge and itching than complete pregnancy group. This is in agreement with a recent study which reported that women with recurrent pregnancy loss, had higher pelvic pain and vaginal bleeding (7). While the risk of threatening abortion was highest among those who reported abdominal discomfort (55.9%), those who did not report pain (42.6%) nevertheless had an abortion.…”
Section: Discussionsupporting
confidence: 92%
“…While the risk of threatening abortion was highest among those who reported abdominal discomfort (55.9%), those who did not report pain (42.6%) nevertheless had an abortion. (7).…”
Section: Discussionmentioning
confidence: 99%
“…7 The most common location of a placenta in a pregnancy, not complicated by previa, is anterior. 8 Other normal locations of the placenta include posterior, lateral, or fundal. There are varying degrees of placenta previa including “total,” “partial,” and “marginal.” 7 A total previa describes the placenta completely covering the internal cervical os whereas partial and marginal previas describe the placenta either partially covering or lying just next to the internal cervical os, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…7 The most common location of a placenta in a pregnancy, not complicated by previa, is anterior. 8 Other normal locations of the placenta include posterior, lateral, or fundal. There are varying degrees of placenta previa including "total," "partial," and "marginal."…”
Section: Discussionmentioning
confidence: 99%
“…It is common knowledge that the heart rate of an embryo will increase from an average of 97.7 beats per minute at thirty-six to thirty-eight days to 174.7 beats per minute at sixty to sixty-two days, & it is also common knowledge that the embryonic heart rate (HER) will continue to increase by approximately 4 beats per minute every day until eight weeks of gestation. This shows that the measurement of EHR by ultrasound may be helpful in timing early pregnancy in the first trimester, & in addition, bradycardia during the 1st trimester can be linked with a bad prognosis (25) .…”
Section: Embryonic Heart Activitymentioning
confidence: 96%